Substitusi terigu dengan tepung jagung dan tapioka dalam pembuatan mie instan protein tinggi: kajian dari penambahan soy protein isolate (SPI) dan Na-alginat - Sukamto Sukamto; Jemi Arrohman; Sudiyono Sudiyono (Program Studi Ilmu dan Teknologi Pangan, Universitas Yudharta, Pasuruan, 2020)
The use of vegetable protein has been developed to increase the protein content of instant noodles. Indonesia is one of the countries that consumes noodles in second place after China. These conditions led to an increase in wheat imports. In an effort to increase the protein content in instant noodles and also reduce the need for wheat, alternative local raw materials are needed to substitute wheat flour. The aim of the study was to utilize tapioca and corn flour as a substitute for wheat flour in the manufacture of instant noodles, which added soybean protein isolate (SPI) and Na-alginate to increase protein content and physical properties. Factorial randomized block design (RBD) was used in this research, factor I was SPI and factor II Na-alginate. The treatment was repeated 3 times. The observational variations were analyzed for variance and continued with the tukey test with α≤ 5% if there was significant. The results showed that the addition of SPI 30% and Na-alginate up to 0.2% increased the protein content of instant noodles to 31.36 ± 0.39% - 34.44 ± 0.34%, water absorption for 5 minutes of cooking was 147 %, cooking time 6.16 ± 0.22 minutes. Overall, the instant noodle is in the category of rather like to like the taste, aroma, color, and texture. Composite flour (corn flour and tapioca) can substitute 50% of wheat flour to produce the instant noodles. The protein contain is 34.44 %, with a contribution of 30% SPI and Na-alginate 0.2%.